Perspektif Islam Tentang Dinasti Politik (Studi Kasus Isu Dinasti Politik Tahun 2023-2024) - Panggabean, Ilham Budiman; Harahap, Aprilinda Martinondang (Jayapangus Press, 2024)
Dynastic politics is a phenomenon that is currently being discussed by Indonesian people amid the 2024 presidential election campaign. This dynastic politics became a trending topic after the Indonesian president's son ran for vice president. The importance of finding a balance between political stability and justice is a major concern in addressing this issue. There are efforts from several elements of society and political activists to advocate for political reform that creates a more transparent and fair system. Therefore, the study of political dynasties that occurred in Indonesia needs to be studied more deeply. The article aims to describe and analyze the issue of political dynasties in Indonesia with a focus on the Islamic political context. This research is a qualitative literature review research with a phenomenological approach to research phenomena that are currently occurring. This research includes an analysis of the historical, structural, and ongoing social impacts of political dynasties within the framework of Islamic politics. The results of this research show that the issue of dynastic politics in Indonesia in 2023-2024 presents complex challenges, especially when viewed from an Islamic political perspective. By understanding these dynamics and seeking solutions that are in line with the principles of justice and democracy, Indonesia can steer itself toward a more inclusive and sustainable political system. In dealing with the issue of dynastic politics, aspects of accountability and transparency become a significant focus from an Islamic political perspective. These principles are considered crucial in protecting power and ensuring political action is by Islamic values. Through this research, it is hoped that it can open people's views to raise calls for political transformation and reform that reflects Islamic values ​​and leads to more just, transparent, and participatory political governance.